Effect of an antioxidant supplement containing high dose lutein and zeaxanthin on macular pigment and skin carotenoid levels - Obana, Akira; Gohto, Yuko; Nakazawa, Risa; Moriyama, Takanobu; Gellermann, Werner; Bernstein, Paul S. (Scientific reports, 2020)
The effect of a high dose lutein/zeaxanthin supplement on macular pigment optical density (MPOD) and skin carotenoid (SC) levels in healthy subjects was investigated. This is a prospective, single-arm, open-label study. Subjects were 16 Japanese, age 26–57 years. Subjects took a supplement containing 20 mg/day of lutein, 4 mg/day of zeaxanthin, and other antioxidants (vitamin C, vitamin E, zinc, copper) for 16 weeks. MPOD levels were measured by a two-wavelength autofluorescence imaging technique. SC levels were measured by reflection spectroscopy. Total volume of MPOD within 9° eccentricity significantly increased by week 8 and continued to increase until week 16 ( p < 0.0001, two-way factorial ANOVA). The increase rate of MPOD was significantly higher in subjects with body mass index (BMI) less than 25 kg/m 2 (n = 13) compared to those of 25 kg/m 2 and higher (n = 3). SC levels increased significantly by week 4 and continued to increase until week 16 ( p < 0.0001, two-way factorial ANOVA). All subjects completed the study without any serious adverse events. These results demonstrated the effectiveness of a high dose lutein/zeaxanthin supplement for MPOD volume and SC levels without serious adverse events.